EVALUATION OF THE QUALITY OF INDIVIDUAL LEARNING PROGRAMMES (PPI) BASED ON INTEGRATED QUALITY MANAGEMENT FROM THE PERSPECTIVE OF ITQAN VALUES: A SEQUENTIAL EXPLORATORY APPROACH AT SD PLUS AL GHIFARI - Uus Ruswandi; Muslikhin Muslikhin; Sam'un Sam'un; Yani Mulyani; Mohammad Aqil Baihaqi (Yayasan Adra Karima Hubbi, 2026)
Inclusive education services through Individualized Education Programs (IEP) often struggle with administrative formalities lacking spiritual depth. This study aims to evaluate IEP quality by integrating Total Quality Management (TQM) and the value of Itqan as a solution for the desecularization of Islamic education management. Employing a mixed-methods sequential explanatory design at SD Plus Al Ghifari, data were collected via questionnaires from 66 respondents and in-depth interviews with key informants. Quantitative findings indicate that both TQM and Itqan significantly influence IEP quality, with Itqan providing a dominant contribution (0.528). Qualitative findings reveal that program effectiveness is driven by a culture of muraqabah (divine consciousness) and daily muhasabah (self-reflection), transforming professionalism into a form of worship. In conclusion, integrating transcendental dimensions into modern managerial systems creates a Spiritual Quality Management model that ensures precision and accountability for students with special needs. This study recommends internalizing Islamic work ethics as a primary catalyst for quality assurance in inclusive Islamic educational institutions.